AN ANALYSIS FOR THE IMPACT OF VERIFIED GROSS MASS IMPLEMENTATION ON PORTS AND EXPORTERS AND A POLICY PROPOSAL: “DEMOCRATIC WEIGHING” - Hüseyin Topuz; Hüseyin Ali Ersoy (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
This study aims to determine the deficiencies of the application for the determination of the verified gross mass in container transport, to conduct a survey on these shortcomings and to propose solutions through survey results. In this study, it has been found out that Verified Gross Mass Implementation is useful, it does not affect port operations adversely, it is beneficial to bring a ceiling fee to the weighing fee, and it brings extra costs and workload to the exporter. In addition, the survey results were supported with the democratic weighting that has been newly presented to the literature. Democratic Weighing is defined as determining a weighing fee according to the goods’ price, quantity, weight of the products that producers produce, and the type of the product which is most loaded from the ports. In this way, both small-scale and value-producing firms will be supported, and a more competitive structure will be provided for growth path and a fair-trade environment will be provided through democratic weighing.